2006
DOI: 10.1111/j.1525-1594.2006.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Intermittent and Continuous Measurement of Cardiac Output After Acute Normovolemic Hemodilution in Pigs

Abstract: Continuous cardiac output (CO) and mixed venous oxygen saturation (SvO2) determined through the pulmonary artery catheter may be helpful in monitoring hemodynamic conditions in critically ill patients. This study aimed to evaluate CO and SvO2 in a model of acute normovolemic hemodilution (ANH), analyzing the accuracy of the continuous versus intermittent method for CO and SvO2 measurement in pigs. Twenty-three pigs were enrolled to three groups: control, ANH with 6% hydroxyethyl starch (HES), or ANH with lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Immediately after beginning CPB, the radial artery pressure was slightly higher than the pressure in the aortic root. At this moment there is severe hemodilution due to the 2 liters of Ringer's lactate added to the circulation, causing an abrupt reduction in hematocrit and consequent reduction in blood viscosity and systemic vascular resistance 13 , which could compensate the vasoconstriction induced by hypothermia and release of inflammatory mediators during CPB 6,7 . During the CPB, great part of the crystalloid in the perfusate leaks to the extravascular space as a consequence of the systemic inflammatory reaction induced by the CPB 14 , which might increase the hematocrit and blood viscosity, contributing to the increase in vascular resistance in the smaller arteries, which would justify the beginning and maintenance of the aorta-to-radial artery pressure gradient at 3 to 5 mmHg, even after discontinuation of the CPB 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after beginning CPB, the radial artery pressure was slightly higher than the pressure in the aortic root. At this moment there is severe hemodilution due to the 2 liters of Ringer's lactate added to the circulation, causing an abrupt reduction in hematocrit and consequent reduction in blood viscosity and systemic vascular resistance 13 , which could compensate the vasoconstriction induced by hypothermia and release of inflammatory mediators during CPB 6,7 . During the CPB, great part of the crystalloid in the perfusate leaks to the extravascular space as a consequence of the systemic inflammatory reaction induced by the CPB 14 , which might increase the hematocrit and blood viscosity, contributing to the increase in vascular resistance in the smaller arteries, which would justify the beginning and maintenance of the aorta-to-radial artery pressure gradient at 3 to 5 mmHg, even after discontinuation of the CPB 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Denise Otsuki et al. (26) of the University of Sao Paulo Medical School (Sao Paulo, Brazil) evaluated continuous cardiac support (CO) and mixed venous oxygen saturation (VOS) in a porcine model of acute normovolemic hemodilution (ANH) to evaluate hemodynamic conditions. The use of continuous and intermittent measurements of VOS showed clinical applicability and good agreement, an effect not reproduced by the CO measurement.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…73 In some recent experimental studies, acute normovolemic hemodilution was well tolerated, which corroborates tolerance to anemia. [74][75][76] Fantoni DT et al 74 showed in a study with 18 dogs that the hemodynamic response to acute normovolemic hemodilution was characterized by improvement of the cardiac index, independent of the evaluated anesthetic agent. Otsuki DA et al 75 published an experimental study with pigs submitted to normovolemic hemodilution.…”
Section: Transfusion In Heart Diseasementioning
confidence: 99%
“…[74][75][76] Fantoni DT et al 74 showed in a study with 18 dogs that the hemodynamic response to acute normovolemic hemodilution was characterized by improvement of the cardiac index, independent of the evaluated anesthetic agent. Otsuki DA et al 75 published an experimental study with pigs submitted to normovolemic hemodilution. In this model, the acute normovolemic hemodilution promoted a decrease in SVO 2 and an increase in cardiac output values.…”
Section: Transfusion In Heart Diseasementioning
confidence: 99%